The Dilemmas of Measuring the Regional Socio-Economic Development: A Case Study of Poland - Elżbieta OCIEPA-KICINSKA; Rafał CZYZYCKI; Piotr SZKLARZ; Rafał KLOSKA (Communications of International Proceedings, 2020)
Processes of social, economic, and regional development are of interdisciplinary nature and they are described by a host of definitions. The academic literature on the subject also emphasises the specific subjectivity of measuring such phenomena, predominantly determined by the lack of up-to-date and universal measures dedicated for this process. Analysing the literature on the subject as well as studies conducted on a national and international scale, it is possible to notice there is no measure dedicated for evaluation of a regional level of socio-economic development, which is adequate for Poland (or other countries at a similar level of development). This article aims at analysing the level of socio-economic development of individual regions in Poland. To this end, a relative coefficient of regional socio-economic development was constructed, which takes into account a broad, up-to-date set of factors of regional socio-economic development. The research study covers the years 2010 – 2018 and consists of three stages: preparing a comprehensive set of variables that describe regional socio-economic development, analysing the input data by means of the linear ordering method based on the data prepared with the zero unitarisation method and the relative coefficient of regional socio-economic development, and analysing the regional well-being ranking according to OECD, including verification of the correlation level of both rankings results. The analysis of the relative coefficient of regional socio-economic development demonstrated increasing discrepancy between the highest and lowest values for the individual regions is astonishing. The presented findings confirm the extreme ranking positions taken by the particular regions, as a result of applying various research methods.
Keywords: Economic Cohesion; Regional Policy; Economic Governance; Social Governance.